Sex change and its registration on the Personal Identity Registry. The change that Constitutional Court did not dare to approve - Eguiguren Praeli, Francisco José (2015)
In this article, the author tries to clarify various aspects of the fundamental right to Personal identity, this with regard to a recent sentence by the Peruvian Constitutional Court which dismissed the claim of a citizen to register in the National Registry of Identification and Civil status his sex change. Also, the autor analyze the arguments that the Court used to make this decision, as well as also used by two of its judges who expressed their disagreement through unique votes. it is point outs that in Peru, as in other countries, there isn’t a law regulating to the registration of sex change. However, for the author this should not limit the Constitutional Court to approve this change.